Penerapan Zerotier Dalam Membangun File Server Pada Kantor Desa Dusun Baru II Kabupaten Bengkulu Tengah - Aan Marsela; Khairil Khairil; Hari Aspriyono (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
Dusun Baru II Village is one of the villages in Central Bengkulu Regency that has internet access and several computer equipment to assist with data processing at the village office. This research aims to utilize existing internet access at Dusun Baru II Village Office to make it easier for every staff member to manage, control and store village official files on server, also known as a file server. The implementation of zerotier in designing file server at Dusun Baru II Village Office, Central Bengkulu Regency was successfully carried out where every employee at Dusun Baru II Village Office had their own account and storage folder on the server so that they could help in managing, controlling and storing village device files on server via Network ID Zerotier 61b565387aaa1adb. The file browser is used for file management on the server, where each user will have its own storage folder on the server, so that one user cannot see the contents of another user's storage folder. Based on the tests carried out, the results showed that the implementation of zerotier in d a file server at the Dusun Baru II Village Office, Central Bengkulu Regency was running well.